Exploring Urban Space: Volumetric Site Analysis for Conceptual Design in the Urban Context. (June 2013) - Leidi, Michele; Schlüter, Arno
This paper proposes a set of new analytic and visualization methods for conceptual design in the urban context. The methodology is based on the discretization of the urban site into a volumetric grid of points. For each of these points, different physical properties such as solar radiation, airflow, and visibility are computed. Subsequently interactive visualization techniques allow the observation of the site at a volumetric, directional and dynamic level, making visible information that is typically invisible. Several case-studies demonstrate how this allows to generate suggestions, for example, for the definition of the form of a building or for the rationalization of its surfaces. This approach aims at developing a conceptual design process that allows the fusion of active technologies, passive methods, and expressive aspects, in cohesive concepts able to embrace and exploit the diversities of an urban site.